Biofluorometric Ear-Gas Sensing for Non-Invasive Monitoring of Blood EtOH - Mitsubayashi, Kohji; Ichikawa, Kenta; Iitani, Kenta (Meeting abstracts (Electrochemical Society), 2024)
Exhaled breath and transcutaneous gas contain volatile organic compounds (VOCs) from blood [1]. Some of these blood VOCs are the resultant products of diseases or metabolisms, which has been attracting significant attention to utilize these VOCs for non-invasive and simple disease screening and metabolism assessment [2,3]. Transcutaneous gas is more suitable to real-time and continuous assessment than breath. Especially, the external ear region has skin with a lower density of sweat glands (140 spots/cm 2 ) compared to other regions of the body, such as the palm, forearm, and cheek. Also, gas from the external ear is not only from an outer part of the external ear but also from the external ear canal. In addition, the external ear has a relatively large space to incorporate devices to measure. In this study, a headset-type ear-gas sensing system including a bio-fluorometric gas sensor has developed using ADH (alcohol dehydrogenase) for external ear-derived EtOH, then the system was applied for continuous measurement of EtOH at the external ear after drinking. The gas monitoring system was developed by combining an over-ear gas collection cell and a biofluorometric gas sensor for EtOH vapor. Alcohol dehydrogenase (ADH) catalyzes the oxidation of EtOH to produce acetaldehyde. Simultaneously, a coenzyme, oxidized form of β-nicotinamide adenine dinucleotide (NAD + ), accepts the electron to become the reduced form (NADH) that exhibits autofluorescence (λex=340 nm, λfl=490 nm); therefore, EtOH can be measured by detecting the increase in the autofluorescence from NADH. An enzyme-immobilized membrane (ADH membrane) attached to the flow-cell worked as a gas-liquid diaphragm. When the EtOH vapor reaches the ADH membrane, the catalyzed redox reaction occurs at the membrane together with NAD + in the buffer solution running above the membrane, which produces NADH in the buffer solution. The resultant NADH was excited by the UV light from the optical fiber, then the emitted fluorescence was collected by the same fiber probe to be detected. In the monitoring of external ear-gas, the sample gas from a subject was collected by the headset type gas collection cell, and then simultaneously transported to the biofluorometric gas sensor for real-time measurement. The gas sensor was composed of excitation and detection units which were connected to a bifurcated optical fiber. The excitation unit has a UV-LED (340 nm) and a bandpass filter (BPF) to make the peak wavelength of the excitation light 340 nm. The detection unit has a photomultiplier tube (PMT) and another BPF to extract fluorescence light from NADH. The flow cell made of PMMA is attached to an optical fiber probe end, that is connected to the bifurcated optical fiber. ADH membrane was attached and fixed at the end of the flow cell by an o-ring. ADH was immobilized by entrapping in a hydrophilic PTFE membrane with poly[2-methacryloyloxyethyl phosphorylcholine (MPC)-co-2-ethylhexyl methacrylate (EHMA)] (PMEH). The sensitivity of the ADH gas sensor and the reproducibility of the sensor output for various ethanol concentrations were investigated. The sensor output was dependent on the concentration of gaseous EtOH. The dynamic range of the ADH gas sensor is 10 ppb-554 ppm of EtOH vapor. The biofluorometric gas sensor indicated the high selectivity, relying on ADH specificity, to gaseous EtOH. The biofluorometric EtOH gas sensor was applied for ear gas sensing.The over-ear gas collection cell was fabricated by modifying a commercial earmuff with two connectors for filtered air (carrier gas) and for sample gas containing ear gas, respectively. Real-time and continuous measurement of external ear-derived EtOH was conducted for healthy subjects with alcohol intake (Approval No. M2018-160 at Tokyo Medical and Dental University). As the results of the ear gas monitoring for the subjects. The EtOH concentration from the external ear started to rise a few minutes after drinking and reached the peak (approx. 100 ppb) 50 minutes later, then the EtOH concentration gradually decreased. This temporal change has a similarity to that of breath EtOH concentration with a few minutes time-delay. According to other reports proving that EtOH concentrations in blood and breath correlate, the concentration of the external ear’s EtOH is most likely correlated to that in blood. In this study, the headset type ear gas sensor successfully measured the transcutaneous ear EtOH-related blood one after drinking. In the future, the ear-gas sensor will be applied to other blood VOCs monitoring for non-invasive assessment of metabolisms and disease conditions that require detailed and real-time information. References [1] Amann, et al. J. Breath Res. 2014, pp. 8. [2] Buszewski, et al. Bioanalysis, 2013, pp. 2287–2306. [3] H. Jalal, et al. ACS Sensors, 2018, pp. 1246–1263. Figure 1